Subjective Health and Factors of Health-related Quality of Life in Elderly Haenyo - Myungah Chae; Jeung Im Kim; Kyung Sook Choi; Ki Hye Han (Korean Society of Women Health Nursing, 2018)
PURPOSE: To investigate the subjective health and health-related quality of life (HRQoL) in Haenyo. METHODS: Subjects were 100 elderly Haenyo in Jeju island who belonged to a fishing-village society. Main variables were activities of daily living (ADL), instrumental ADL (IADL), the HRQoL, subjective health, and depression. Subjective health and differences of HRQoL by variables were analyzed by t-test or ANOVA using IBM SPSS Statistics 23. Hierarchical multiple regression was executed to examine the effects of the major factors on the quality of life. RESULTS: The mean age was 69.9 years, the mean period for diving career was 51.5 years, and work hours per month were 37.8. Comorbidity of diseases was 2.74, and the common health problems were osteoporosis and headache/dizziness. HRQoL was significantly different by age (F=4.52, p=.013), education (F=6.10, p=.003), muljil work years (F=3.93, p=.050), depression (t=-3.04, p=.030), subjective health state (F=30.62, p < .01), and degenerative arthritis (F=-2.38, p=.019). In the final model by hierarchical multiple regression, ADL/IADL (β=.41, p < .001), depression (β=-.29, p < .001), and subjective health (β=.43~.51, p < .001) were significant and explained 63.5% of the total variance of HRQoL. CONCLUSION: Haenyo have specific health problems different from those of elderly women in general. ADL/IADL, depression and subjective health affected their HRQoL. It is clear that Haenyos' health problems need further study to improve their health.